2016
DOI: 10.1097/mop.0000000000000311
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced acute kidney injury in neonates

Abstract: Purpose of review Acute kidney injury (AKI) is an independent risk factor for morbidity and mortality in critically ill neonates. Nephrotoxic medication exposure is common in neonates. Nephrotoxicity represents the most potentially avoidable cause of AKI in this population. Recent findings Recent studies in critically ill children revealed the importance of recognizing AKI and potentially modifiable risk factors for the development of AKI such as nephrotoxic medication exposures. Data from critically ill chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 69 publications
(75 reference statements)
0
45
0
3
Order By: Relevance
“…In these settings, the healthy regulation of blood flow via dilatation of the afferent by prostaglandins and vasoconstriction of both efferent and afferent renal vessels by angiotensin is often inhibited resulting in oliguria [40]. Nephrotoxic insults commonly occur from medications, such as antibiotics, antifungals, non-steroidal anti-inflammatory drugs, and diuretics [41]. Despite limited studies to support its use, diuretics are commonly used to reduce ventilatory and oxygen requirements, and methylxanthines like caffeine are ubiquitous, due to the proposed beneficial short and long-term effects on respiratory and developmental status [42].…”
Section: Reviewmentioning
confidence: 99%
“…In these settings, the healthy regulation of blood flow via dilatation of the afferent by prostaglandins and vasoconstriction of both efferent and afferent renal vessels by angiotensin is often inhibited resulting in oliguria [40]. Nephrotoxic insults commonly occur from medications, such as antibiotics, antifungals, non-steroidal anti-inflammatory drugs, and diuretics [41]. Despite limited studies to support its use, diuretics are commonly used to reduce ventilatory and oxygen requirements, and methylxanthines like caffeine are ubiquitous, due to the proposed beneficial short and long-term effects on respiratory and developmental status [42].…”
Section: Reviewmentioning
confidence: 99%
“…The management of neonates in intensive care often requires a combination of various therapeutic agents, frequently unlicensed or off-label, with many of them potentially inducing renal tissue injury [397,398]. Antibiotics (aminoglycosides and vancomycin), antifungals (amphotericin B), antivirals (acyclovir), angiotensin-converting enzyme inhibitors, and NSAID can induce nephrotoxic damage through several concomitant mechanisms of action on different segments of the nephron and may directly impair any ongoing nephrogenesis in a preterm infant [136,141,143,146]. A retrospective review found that 87% of neonates in ICU were exposed to at least 1 nephrotoxic medication for an average duration of around 2 weeks [141].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Others have reported higher serum creatinine values at 2 months of age in preterm infants born SGA who received aminoglycosides compared with those who did not [152]. Given that many infants receive multiple medications, and that infants with the lowest birth weights tend to receive more nephrotoxic medications per day, increased awareness of risks and of potential interventions to minimize the risk of toxicity are crucial [136,141,146,147]. A medication that is frequently used in the neonatal ICU that may be protective against AKI is caffeine, but more study is required to better determine the true effect [153].…”
Section: Introduction To a Health Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Using serum creatinine to define AKI is particularly ineffective in the neonatal period given a rapidly changing GFR in the first two weeks of life with alterations in renal blood flow [46]. Premature neonates are suspected to be at an even higher risk for development of any cause AKI given renal underdevelopment, which should encourage limited use of nephrotoxic agents [47]. Although much remains unknown regarding specific nephrotoxic agents used in the newborn period, neonates are known to have an increased susceptibility to aminoglycoside-associated AKI [26].…”
Section: Who Is At Risk For Drug-associated Aki?mentioning
confidence: 99%